2022
DOI: 10.1002/aesr.202200075
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Driven Cu─Pd Bond Formation to Enhance the Efficiency for Electroreduction of CO2 to CO

Abstract: The redox reaction as the driving force induces the dynamic structure of the electrocatalyst, which enhances the performance of the catalysis. Yet, it lacks the understanding of the influence of redox driving force on the transforming process, inhibiting obtaining the actual factor that determines the catalytic performance. Resorting to the pulse and in situ methodology, herein, the effect of spontaneous reoxidation on the structural transformation of the Cu–Pd bimetallic catalyst for CO2 electroreduction is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, at each potential above −0.35 V, the Raman shift discerned the *CO-binding strength in Cu 2 O and Cu 2 O@Pd x catalysts: the apparent red shift of the top-bound-*CO peak from Cu 2 O to Cu 2 O@Pd 3.14 , deciphering the intensification of the top-bound-*CO binding strength because of the back-𝜋-donation effect. [21,57,58] This finding indicated that the presence of various (sub)surface oxygen varied *CO binding strength, and accordingly, tuned the energy barrier for the multi-carbon production reaction. [10,12,18] Nevertheless, one assumption should be considered: as Pd nanoparticle is the CO-favoring electrocatalyst, [66] the tandem effect driven by the addition of Pd is likely to increase the *CO coverage and enhance the multi-carbon production.…”
Section: The Interplay Of the (Sub)surface Oxygen And The *Co Couplin...mentioning
confidence: 85%
See 2 more Smart Citations
“…However, at each potential above −0.35 V, the Raman shift discerned the *CO-binding strength in Cu 2 O and Cu 2 O@Pd x catalysts: the apparent red shift of the top-bound-*CO peak from Cu 2 O to Cu 2 O@Pd 3.14 , deciphering the intensification of the top-bound-*CO binding strength because of the back-𝜋-donation effect. [21,57,58] This finding indicated that the presence of various (sub)surface oxygen varied *CO binding strength, and accordingly, tuned the energy barrier for the multi-carbon production reaction. [10,12,18] Nevertheless, one assumption should be considered: as Pd nanoparticle is the CO-favoring electrocatalyst, [66] the tandem effect driven by the addition of Pd is likely to increase the *CO coverage and enhance the multi-carbon production.…”
Section: The Interplay Of the (Sub)surface Oxygen And The *Co Couplin...mentioning
confidence: 85%
“…This phenomenon, as indicated in Figure 8c, evidently highlighted the important roles of kinetically-stabilized (sub)surface oxygen stemming from the dynamic oxygen diffusion in catalysts (solid) or the re-oxidation process, which considered the overall contribution of oxygen species in the electrolyte (liquid) such as hydroxide, water molecules, or the dissolved oxygen gas. [20,57,58] Accordingly, both oxygen species in electrolyte and dynamic (sub)surface-oxygen were going to stabilize the high-valent Cu 𝛿 + species, indicating that re-oxidation behavior greatly dominated the surface high-valent Cu 𝛿 + species and resulting product profile of CO 2 RR. By our methodology and discussion, the PdO x could serve as a surface probe for oxygen because of the (sub)surface oxygen bound to both Pd and Cu sites.…”
Section: The Interplay Of the (Sub)surface Oxygen And The *Co Couplin...mentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the Pd–M coordination numbers in fcc -PdCu/C are 5.3 and 7.5 at 2.637 and 2.709 Å, respectively. The coordination numbers of the first layer in bcc -PdCu/C and fcc -PdCu/C correspond to bcc and fcc structures, respectively. , Considering that the Pd–Cu bond is shorter than the Pd–Pd bond in the same crystal structure, the close coordination number of the two bond lengths in fcc -PdCu/C indicates the coexistence of Pd–Cu and Pd–Pd bonds. , Moreover, HRTEM images (Figure S6) indicated that lattice distances of 0.214 nm ( bcc -PdCu) and 0.217 nm ( fcc -PdCu) correspond to the {110} facet of bcc PdCu and the {111} facet of fcc PdCu, respectively.…”
mentioning
confidence: 96%
“…29,34 Considering that the Pd− Cu bond is shorter than the Pd−Pd bond in the same crystal structure, the close coordination number of the two bond lengths in fcc-PdCu/C indicates the coexistence of Pd−Cu and Pd−Pd bonds. 29,35 Moreover, HRTEM images (Figure S6) indicated that lattice distances of 0.214 nm (bcc-PdCu) and 0.217 nm (fcc-PdCu) correspond to the {110} facet of bcc PdCu and the {111} facet of fcc PdCu, respectively. Moreover, the surface properties were studied by using X-ray photoelectron spectroscopy (XPS).…”
mentioning
confidence: 99%